Case Report: Desmoid fibromatosis in the mediastinum of a 6-month-old toddler, what to do? - Endara, Santiago A.; Dávalos, Gerardo A.; Molina, Gabriel A.; Armijos, Christian A.; Narvaez, D. Sebastian; Montalvo, Nelson (Frontiers in Surgery, 2023)
Desmoid fibromatosis is a rare, aggressive borderline lesion arising from soft tissues. Treatment will depend on the structures that the tumor has involved. Surgery with negative margins is the recommended strategy as it can usually achieve disease control; however, the tumor's location sometimes does not allow it. Therefore, a combination of medical therapies along with strict surveillance is crucial. We present the case of a 6-month-old boy with a chest mass. After further evaluation, a rapidly growing mediastinal mass involving the sternum and costal cartilage was detected. Desmoid fibromatosis was the final diagnosis.